AMP-Activated Protein Kinase: Structure and Regulation - Sanz, Pascual (Current Protein and Peptide Science, 2008)
Mammalian AMP-activated protein kinase (AMPK) is a serine/threonine protein kinase that acts as a sensor of cellular energy status. It is activated by a large variety of cellular stresses that increase cellular AMP and decrease ATP levels and also by physiological stimuli, such as muscle contraction, or by hormones such as leptin and adiponectin. AMPK modulates multiple metabolic pathways. As a result, it has become a target for the development of new drugs for the treatment of type II diabetes, obesity or even cancer. In fact, it has been recently reported that drugs used in the treatment of diabetes, such as metformin and thiazolidinediones (TZDs), exert their beneficial effects through the activation of AMPK. AMPK is a heterotrimeric complex composed of a catalytic subunit (AMPK-α) and two regulatory subunits (AMPK-β and AMPK-γ). Functional orthologues of this kinase complex are found throughout eukaryotic kingdom, from yeast to humans, indicating that the function of this complex is evolutionarily conserved. This review summarizes the recent studies on the structure and regulation of the AMPK heterotrimeric complex.
Keywords: CaMKK